Dynamic Modeling and Control Optimization of Free-Floating Dual-Arm Space Robots in Task Space - Rodrigues, Gabriel S.; Pazelli, Tatiana F. P. A. T. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
The development of orbital space robotics in recent decades is aimed at meeting the demand for extravehicular missions, such as supply, maintenance, inspection, rescue and material transport. A space manipulator can be defined as one or more arms coupled to a floating base (satellite) for operation in orbit. The differential characteristic of these systems is the dynamic coupling existing between the base and the manipulators, which makes it difficult the independent analytical parameterization of the kinematics of its end-effectors. In this article, a mathematical modeling of the dynamics of the two-arm free-floating space robot structurally identical to the closed matrix format consolidated in the literature for single-arm robots is formulated. The dynamic coupling between the two arms and the base is resolved by the law of conservation of momentum, valid for isolated systems described in inertial frames. Due to the sharing of mathematical properties with the single-arm case, the proposed model can be validated in the task space through the Computed Torque approach. The modularity of the proposed model suggests an immediate extension to scenarios with multiple arms and floating base, which should present even more reliability and operational range than two-arm robots.